Quantifying Missed Opportunities for Recruitment to Home Dialysis Therapies. (February 2021) - Poinen, Krishna; Er, Lee; Copland, Michael A.; Singh, Rajinder S.; Canney, Mark
Background: Despite the recognized benefits of home therapies for patients and the health care system, most individuals with kidney failure in Canada continue to be initiated on in-center hemodialysis. To optimize recruitment to home therapies, there is a need for programs to better understand the extent to which potential candidates are not successfully initiated on these therapies. Objective: We aimed to quantify missed opportunities to recruit patients to home therapies and explore where in the modality selection process this occurs. Design: Retrospective observational study. Setting: British Columbia, Canada. Patients: All patients aged >18 years who started chronic dialysis in British Columbia between January 01, 2015, and December 31, 2017. The sample was further restricted to include patients who received at least 3 months of predialysis care. All patients were followed for a minimum of 12 months from the start of dialysis to capture any transition to home therapies. Methods: Cases were defined as a "missed opportunity" if a patient had chosen a home therapy, or remained undecided about their preferred modality, and ultimately received in-center hemodialysis as their destination therapy. These cases were assessed for: (1) documentation of a contraindication to home therapies; and (2) the type of dialysis education received. Differences in characteristics among patients classified as an appropriate outcome or a missed opportunity were examined using Wilcoxon rank-sum test or χ 2 test, as appropriate. Results: Of the 1845 patients who started chronic dialysis during the study period, 635 (34%) were initiated on a home therapy. A total of 320 (17.3%) missed opportunities were identified, with 165 (8.9%) having initially chosen a home therapy and 155 (8.4%) being undecided about their preferred modality. Compared with patients who chose and initiated or transitioned to a home therapy, those identified as a missed opportunity tended to be older with a higher prevalence of cardiovascular disease. A contraindication toboth peritoneal dialysis and home hemodialysis was documented in 8 "missed opportunity" patients. General modality orientation was provided to most (71%) patients who had initially chosen a home therapy but who ultimately received in-center hemodialysis. These patients received less home therapy–specific education compared with patients who chose and subsequently started a home therapy (20% vs 35%, P < .001). Limitations: Contraindications to home therapies were potentially under-ascertained, and the nature of contraindications was not systematically captured. Conclusions: Even within a mature home therapy program, we discovered a substantial number of missed opportunities to recruit patients to home therapies. Better characterization of modality contraindications and enhanced education that is specific to home therapies may be of benefit. Mapping the recruitment pathway in this way can define the magnitude of missed opportunities and identify areas that could be optimized. This is to be encouraged, as even small incremental improvements in the uptake of home therapies could lead to better patient outcomes and contribute to significant cost savings for the health care system. Trial Registration: Not applicable as this was a qualitative study.